Perspectives of health service providers in delivering best-practice care for Aboriginal mothers and their babies during the postnatal period - Jocelyn Jones; Angela Durey; Natalie Strobel; Kimberley McAuley; Karen Edmond; Juli Coffin; Daniel McAullay (BMC, 2023)
Abstract Background Evidence suggests that Aboriginal babies in Western Australia are not receiving adequate primary health care in their first 3 months of life, leading to questions about enablers and constraints to delivering such care. This paper presents findings from a qualitative research project investigating health providers' perceptions and experiences of best and current practice in discharge planning, postnatal care and health education for Aboriginal mothers and their newborn babies. Methods Constructivist grounded theory guided this research involving 58 semi-structured interviews conducted with health providers who deliver care to Aboriginal mothers and infants. Participants were recruited from hospital-based and primary health sites in metropolitan Perth, and regional and remote locations in Western Australia. Results Structural factors enabling best practice in discharge planning, postnatal care, and health education for mothers included health providers following best practice guidelines and adequate staffing levels. Organisational enablers included continuity of care throughout pregnancy, birth and postnatally. In particular, good communication between services around discharge planning, birth notifications, and training in culturally respectful care. Structural and organisational constraints to delivering best practice and compromising continuity of care were identified as beyond individual control. These included poor communication between different health and social services, insufficient hospital staffing levels leading to early discharge, inadequate cultural training, delayed receipt of birth notifications and discharge summaries received by Aboriginal primary health services. Conclusion Findings highlight the importance of examining current policies and practices to promote best practice in postnatal care to improve health outcomes for mothers and their Aboriginal babies.